A Comparison of Different Tournament Weigh‐In Formats on the Short‐Term Postrelease Behavior of Black Bass Assessed with Biologgers. (8th February 2022) - LaRochelle, Luc; Trahan, Alexandria; Brownscombe, Jacob W.; Danylchuk, Andy J.; Cooke, Steven J.
Abstract: Black bass Micropterus spp. live‐release tournaments are a popular activity in North America. Efforts continue to further increase survival and enhance welfare of fish released from competitive angling events. Recently, some tournaments have adopted a new weigh‐in format in which black bass are weighed immediately (hanging from a scale in air) and released at the capture location. More conventional tournaments involve retaining black bass in a live well and delivering them to a central location to be weighed (wet or dry weigh‐in). We used biologgers that measured swimming activity, depth selection, and water temperature selection to examine how different weigh‐in formats alter postrelease behavior of Smallmouth Bass M . dolomieu and Largemouth Bass M. salmoides . All fish showed a significant decrease in swimming activity as time progressed during the 10‐min monitoring period, regardless of the weigh‐in format. Swimming activity remained elevated (i.e., hyperactivity) for a longer period of time for black bass that were retained in live wells compared to those that were subjected to the catch, weigh, and release weigh‐in format and the control (fish that were caught and immediately released without air exposure). Swimming activity of black bass tended to decrease as they achieved greater depths with cooler water temperatures. For both species, the water temperature selected postrelease was influenced by the weigh‐in format. Black bass that were dry weighed and wet weighed spent more time in warmer water temperatures than fish in the control group or fish that were caught, weighed, and released. This study suggests that to reduce behavioral alterations associated with wet or dry weigh‐ins, tournament organizations need to carefully select the weigh‐in location, allowing easy access to refuge (i.e., habitat complexity similar to that of the capture location) having the cooler water temperatures commonly associated with deeper water. These results also suggest that catch, weigh, and release formats could be beneficial for black bass during periods of the year with elevated water temperature.